The Difference Between a Man and a Woman - Lang, Theo (New York The John Day Company, 1971)
The force exerted by a womans hand is on average about one third less than that exerted by a mans hand"" which is all that kept us from tearing this book in half. Mr. Lang (a newspaperman and author of The Darling Daisy Affair, no great work of scholarship either) has collected the ""richest nuggets"" from various disciplines to trace the differences from the chromosome on, roughly physical, intellectual and social. One may be bemused by a second chapter on ""The Mystery of Menstruation"" after an interval of about 100 pages. Early on you will get both the personal inflection as well as distortion- ""I prefer to believe that the uttering of Dadda precedes the uttering of Mamma because Dadda is usually the first person the baby actually sees and recognizes as an individual."" But Lang also relies on other sources (acknowledged in the text) whether its Freud or Raquel Welch, Margaret Mead or the ""brilliant Mrs. Pearl Craigie"" whoever she is. In general women are not brilliant although they have a higher I.Q. (he says): still there are no great women ""creative genius""es since women are too ""personally involved in sensations and emotions to be objectively creative."" We found it difficult to understand how creativity could be objective, just as difficult as most of the silly suppositions in this book- a work of some factual appropriation along with vive-la-difference enthusiasms and misconceptions.
Keywords: Literature